PEMBERDAYAAN WANITA MELALUI USAHA KRUPUK LELE ORGANIK DI DESA SUMBERNGEPOH, LAWANG KABUPATEN MALANG - Suhartatik Suhartatik; Titik Purwati; Wilyati Agustina Bangun (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2021)
Women's empowerment is the focus of this community service activity in partnership with mothers from the Krupuk Business Group, Ibu Mujiati and Ibu Tuni. The purpose of this activity is to solve the problems faced by the organic catfish cracker business group partners in Sumberngepoh Village, Lawang, Malang Regency, in terms of production and management aspects. The targets to be achieved from this activity are training and additional production equipment for partners as an effort to empower the community. Method of program implementation This activity goes through three stages, namely the planning stage, the implementation stage and the evaluation stage. The results achieved from this activity are: 1) a solution to production problems by adding/procuring new production equipment and raw materials for making organic catfish crackers; 2) the existence of solutions to management problems by holding management training which includes production, marketing, sanitation and hygiene. The final result shows that there are indicators of success with increased knowledge of partners and productivity of organic catfish crackers that increase with management training.